2015
DOI: 10.1016/j.tox.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic p,p′-dichlorodiphenyldichloroethylene (DDE) exposure on high fat diet-induced alterations in glucose and lipid metabolism in male C57BL/6H mice

Abstract: Diabetes mellitus is a highly prevalent metabolic disease affecting 29.1 million people or 9.3% of the population of the United States. The most prevalent form of diabetes is type 2 diabetes (T2D) which comprises 90-95% of all reported cases of diabetes. While the exact cause of T2D remains an enigma, known risk factors include age, weight, sedentary lifestyle, poor dietary habits, and genetic predisposition. However, these risk factors can not sufficiently explain the increasing prevalence of T2D. Recently, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 35 publications
6
35
2
2
Order By: Relevance
“…Exposures to organochlorine insecticides (DDE, HCB, and ɣ-HCH) have led to increased body weight gain in rodents (Table 4) (Chadwick et al, 1988; Howell et al, 2014; Howell et al, 2015; Villeneuve et al, 1977), including a study of parental trans-generational exposure to DDT linked to increased obesity rate in the offspring (Skinner et al, 2013). Similarly, others reported that perinatal exposure to DDT was linked to significant weight gain, but only in female offspring (La Merrill et al, 2014) or reduced weight was reported after dieldrin exposure (Shakoori et al, 1984).…”
Section: Effects Of Insecticide Exposure On Glucose and Lipid Metamentioning
confidence: 99%
“…Exposures to organochlorine insecticides (DDE, HCB, and ɣ-HCH) have led to increased body weight gain in rodents (Table 4) (Chadwick et al, 1988; Howell et al, 2014; Howell et al, 2015; Villeneuve et al, 1977), including a study of parental trans-generational exposure to DDT linked to increased obesity rate in the offspring (Skinner et al, 2013). Similarly, others reported that perinatal exposure to DDT was linked to significant weight gain, but only in female offspring (La Merrill et al, 2014) or reduced weight was reported after dieldrin exposure (Shakoori et al, 1984).…”
Section: Effects Of Insecticide Exposure On Glucose and Lipid Metamentioning
confidence: 99%
“…The 1,1′‐(2,2,2‐trichloroethane‐1,1‐diyl)bis(4‐chlorobenzene) (known as dichloro–diphenyl–trichloroethane, DDT) is a synthetic organochlorine, low‐cost pesticide widely used in the past years against malaria . It exerts its toxicity on the central nervous system altering the functionality of ion channels; many in vivo and in vitro studies have demonstrated adverse effects also on vertebrates including humans, affecting lipid and glucose metabolism and inducing cellular oxidative stress . Though having been banned in rich industrialized countries from ‘70s, it is still used in developing areas of Africa and Asia, where malaria, dengue and other diseases transmitted by mosquitoes are endemic .…”
Section: Introductionmentioning
confidence: 99%
“…In the light of this trend, the risk factors commonly studied fail to explain by themselves the global boom of both diseases. Hence, "non-traditional" risk factors have been reconsidered (Arrebola et al, 2015;Howell et al, 2015). Some epidemiological evidence links general pesticide exposure (Arrebola et al, 2013(Arrebola et al, , 2015Suarez-Lopez et al, 2015) and more specifically OP exposure (Montgomery et al, 2008;Saldana et al, 2007) to a higher incidence of type 2 diabetes and related metabolic dysfunctions.…”
Section: Introductionmentioning
confidence: 99%